Assessing the level of readiness in Tshwane and Dr Kenneth Kaunda Districts for implementing a national patient based information system - Tanna, Gaurang (My University, 2017)
PURPOSE: The National Health Insurance programme has been identified as a priority to achieve Universal Health Coverage in South Africa. The development and implementation of a health information system (HIS) that is underpinned by a master population index (ability to uniquely identify a person), and operates on the electronic health records (EHR) model is critical for the implementation of the NHI. This study assesses the level of readiness in Tshwane and Dr Kenneth Kaunda districts for implementing a national patient based health information system. METHODS: This study design was a descriptive cross-sectional design. The study used a structured questionnaire to measure the level of readiness in two NHI districts, namely, Tshwane and Dr Kenneth Kaunda, for implementing a patient based National Health Information System in South Africa. RESULTS: The assessment has revealed that PHC facilities are at varying levels of readiness for implementing a national patient based information system. Tshwane scored better than Dr Kenneth Kaunda district on all four readiness criteria, with non-significant differences between them for core readiness, engagement readiness, and societal readiness and significantly higher levels in Tshwane for technological readiness. The readiness results varied across all four domains, ranging from 13% and 16% for core readiness to 59% and 68% for engagement readiness for Dr Kenneth Kaunda and Tshwane districts respectively. CONCLUSION: PHC facilities in Tshwane and Dr Kenneth Kaunda districts were capacitated with respect to ICT infrastructure. There were weaknesses with respect to business processes and IT support. The business process for the filing system needs to be defined, optimised and implemented in PHC facilities. The turnaround time for IT support was unacceptably high in both districts and needs to be improved prior to implementation of a patient based information system.
Research Report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the Degree of Master of Public Health. March 2017.
Keywords: Health Information Systems; Electronic Health Records